Escola pública de Cuiabá : colonialidade do saber no ensino da arte, na política educacional e livro pedagógico de arte - Ourives, Mariel de Souza (2016)
The education in Brazil, which keeps the influence from colonization process, concerning about Art’s History, narrated from european paradigms, it built and legitimated for centuries which the argentinean theorist Walter Mingolo understands as epistemic hegemony. To dismantle that "universal naturalization” built from european and north american hegemonic epistemology, which constitutes the core of the theoretical framework Modernity/Coloniality that we adopt on this qualitative research to make reflections about the incidence of Coloniality of Knowledge at Art’s basic teaching education at Cuiabá’s public state schools between the years from 2014 to 2015. And we base upon this theoretical approach and we intend to give evidence and to argue about the legitimated and hegemonic discourses at brazilian and matogrossense educational and pedagogical work, and as well as its appropriation in the curriculum and in the practices which choose this universal canon as the basis from what it ought to be taught at Arts. Therefore, the present scientific work makes a proposal to see and to highlight the visual production from local artists and the academic and critical reflection of an effective local plastic arts movement with the aim to make both of them a possible pedagogical and didactic resource to be incorporate in the curriculum at Mato Grosso´s state public schools. The present sci-entific work is inserted on the research field “Poéticas Contemporâneas”, in the stricto sensu master's course “Estudos de Cultura Contemporânea”.